Teologi Pendidikan Agama Kristen: Fondasi Dan Implikasi Untuk Pendidikan Modern - Yurlina Ndruru; Andreas Teko; Sandra Rosiana Tapilaha (Asosiasi Riset Pendidikan Agama dan Filsafat Indonesia, 2024)
This research aims to explore how Christian Religious Education Theology plays a key role in shaping the foundation for the development of a modern education system based on Christian principles. This theological foundation includes an understanding of Biblical teachings on education, the role of Jesus Christ as the primary example in education, and the Christian perspective on character formation. Its impact involves the application of Christian moral and ethical values in the educational environment, the formation of personalities based on love, and the development of curricula that integrate knowledge with spiritual values. With the proper understanding and application of Christian religious education theology, modern education can produce individuals who are not only academically intelligent but also have strong moral and spiritual integrity, ready to face the challenges of this era. The purpose of this research is to enable students to understand and grow in Christ, so that they can achieve spiritual maturity and be protected from the negative influences of their environment on their faith. The method used is qualitative, where every observed phenomenon in society is described in detail. Data are collected through observation, books, PDF, journals, and documentation. The results of the research show the importance of teaching the divine aspects of Christ in the curriculum of Christian Religious Education.